Burnout syndrome in professors - Rodríguez Ramírez, José Andrés; Guevara Araiza, Albertico; Viramontes Anaya, Efrén (IE Revista de Investigación Educativa de la REDIECH, 2017)
It is an investigation that deals with the phenomenon of occupational stress and its most acute manifestation: Burnout Syndrome. The study was developed in Mexican high school professors. An investigation in Depth inquiry, was made through the phenomenological or interpretive paradigm, the qualitative approach, performed with a single case study method; the techniques used were life history, non-participant observation and interview, and as instruments: the questionnaire and field diary. The main results show an analysis of the problems of this syndrome through four main categories: work-related stress, the professor, the student and the institution. The first explains the essence of how the syndrome is perceived, the remaining three, outline the perception and experience of the problem of the professors and their activities; the student and what implies to share time to professors with this problem and, finally, the institution, in the sense of how it faces what lives inside of it as a result of having the existence of a teacher with these characteristics.